Synthesis and characterization of silver/polyvinilpirrolidone (Ag/PVP) nanoparticles using gamma irradiation techniques - Gasaymeh, Shawkat Salameh; Radiman, Shahidan; Lee, Yook Heng; Saion, Elias; Saeed, G. H. Mohamed (Science Publications, 2010)
Problem statement: In this study, attempts had been made to synthesize silver (Ag)/Poly Vinylpyrolidone (PVP) nanoparticles by ionizing radiation and at the same time overcoming some of the disadvantages previously reported by other methods such as impurities, solvent toxicity, size and distribution control and difficulty in their preparation that limits their commercialization potential. Approach: The use of this alternative method overcomes some unfavorable characteristics like long tedious and costly process, uncontrolled size and distribution. The advantages of radiation processing of the materials relative to other methods are; no metallic catalyst is required; (gives pure product), no oxidizing or reducing agent is required, the process occurs at a liquid or/and solid-state condition, fast and inexpensive, environmental friendly with controllable acquisitions. Results: Ag/PVP nanoparticles were successfully prepared in one-step by γ-irradiation technique in an aqueous system at room temperature and under ambient pressure. The Transmission of Electron Microscopy (TEM) of the as-prepared product particles ranged from 100 to around 8 nm depend on the irradiation dose value, which showed a good distribution with a controlled size as dose changed. The presence of PVP polymer was considered as an important reason that influenced the shape and distribution. The band gap energy was calculated from the UV-VIS absorption spectra. Thermal analysis TGA showed that the composite had a higher degradation temperature than the PVP alone. Conclusion: This result indicated that AgNO3 can effectively dope PVP and enhance the optical and thermal properties. In addition, γ-irradiation is an effective technique for preparing inorganic/organic nanocomposites.